School-based epidemiology study of myopia in Tianjin, China - Wang, Jiaxing; Li, Ying; Zhao, Zhenyang; Wei, Nan; Qi, Xiaoli; Ding, Gang; Li, Xue; Li, Jing; Song, Linlin; Zhang, Ying; Yi, Richard Hyun; Ning, Yuxian; et al. (International ophthalmology, 2020)
Purpose To study the epidemiology of myopia in school-aged children in Tianjin and the relationship between visual acuity-based screening and refraction-based screening. Method This school-based prospective cohort study was performed on children from 42 elementary schools and 17 middle schools in Tianjin, China. Totally 14,551 children, ages ranging from 5 to 16 years, were included in this study. Uncorrected visual acuity (UCVA) was determined by logarithmic tumbling E chart. Non-cycloplegic photorefraction was examined by the Spot (v2.1.4) photoscreener. The relationship between the UCVA and refractive error was investigated for different age groups. Results The overall prevalence of myopia at this school based screen is 78.2%, ranged from 10% at age of 5 to 95% at age of 16. The most dramatic increase in prevalence is from age of 6 (14.8%) to age of 7 (38.5%). The overall prevalence of high myopia is 2.5%. UCVA is found corresponding to spherical equivalent refraction (SER) in a manner of normal distribution and is significantly affected by age. When using UCVA to estimate the prevalence of myopia, the overall sensitivity and specificity are 0.824 and 0.820, respectively. Age-dependent optimal cutoff points and 95% confident intervals of such estimation are reported. Conclusions Myopia is heavily affecting school-aged children in Tianjin, China. The refraction screening is preferable for myopia screening, whereas the UCVA screening results need to be interpreted in an age-dependent manner for myopia estimation.